"HEALING THROUGH ART: ANALYZING THE PSYCHOLOGICAL EFFECTS OF SCULPTURES IN HOSPITAL DESIGN" - Salai Tamilarasan. S , Dr. Rajesh R (South Eastern European Journal of Public Health, 2025)
Healthcare facilities are incorporating sculptures because the healing power of art has been recognized for centuries. This investigation examines the effects of healthcare facility sculptures regarding their effects on patient emotions together with stress reduction and complete experience quality. Through a qualitative research framework, the investigators evaluate the various sculpture types, including abstract examples and nature depictions and human figures, to determine their ability to produce more favourable healthcare spaces for patients along with their families and employees. The researcher will combine Visual observations of selected hospital sculptures with patient interviews and caregiver interviews to evaluate both psychological and physiological reactions. This work presents evidence about how sculptures offer therapeutic potential to improve the care environment within clinical settings while showing how aesthetics supports wellbeing. This research promotes sculptures as basic elements for healthcare designs to aid emotional and psychological healing in addition to medical interventions.